2021
DOI: 10.1182/blood-2021-147483
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the High-Risk Multiple Myeloma Cell Surface Proteome Identifies T-Cell Inhibitory Receptors for Immune Targeting

Abstract: Multiple myeloma (MM) is an incurable malignancy of mature plasma cells. Despite major advances in the therapeutic armamentarium of MM, only 50% of patients survive more than 5 years after diagnosis, with significantly lower rates (21%) for high-risk patients. Chimeric Antigen Receptor (CAR) T-cell therapy targeting BCMA (B-cell maturation antigen) shows high response rates in relapsed/refractory patients. However, most patients have disease remission that lasts less than 18 months, prompting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The identification of new potential targets is a growing field in MM. Oldham et al 21 and Ferguson et al 37 focused on membrane glycoproteins, while Di Meo et al, 38 Anderson et al, 39 and ourselves analyzed the entire set of surface proteins. The obtained datasets were either used alone or combined with transcriptomic datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of new potential targets is a growing field in MM. Oldham et al 21 and Ferguson et al 37 focused on membrane glycoproteins, while Di Meo et al, 38 Anderson et al, 39 and ourselves analyzed the entire set of surface proteins. The obtained datasets were either used alone or combined with transcriptomic datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, each study will not provide the same list of candidates, and candidates must be confirmed by other analyses. For example, Di Meo et al 38 demonstrated 3 proteins (CCR1, LRRC8D, and SEMA4A) whose inactivation individually reduces the in vitro growth of MM cells by ≈60%, 50%, and 50%, respectively. Anderson et al 39 confirmed the unique expression of SEMA4A and found that downregulating its expression using shRNA decreased myeloma cell proliferation, increased apoptosis, and delayed tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Key proteins on the MM cell surface which mediate these interactions have been an area of active research in order to reveal mechanisms for MM transformation and progression [ 11 ]. Furthermore, some of these proteins can be clinically utilized in the management of MM, initially for diagnostic purposes, but also for prognostication and lastly for therapeutic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some of these proteins can be clinically utilized in the management of MM, initially for diagnostic purposes, but also for prognostication and lastly for therapeutic measures. Hundreds of such bioactive surface proteins have been identified and investigated, frequently including immune signaling-related proteins, followed by transporters and adhesion molecules [ 11 ].…”
Section: Introductionmentioning
confidence: 99%